Phǣn phatthanā Khwāmsư̄trong hǣng Chāt Phō̜. Sō̜. 2555-2559 : čhāk Kānprachum Samatchā Khunnatham hǣng Chāt khrang thī 5 pī ngoppramān 2554 (Singphim / Sūn Khunnatham ;, 2012)
Conference papers of the fifth meeting of the National Moral Assembly on the plan for promotion of integrity and ethics in the various organizations in Thailand for 2012-2016.